The effectiveness of regeneration policy in historic urban quarters in England (1997-2010) - Song, Shuang; Oc, T. (2013)
UK cities have been transfonned over the past thirty years as they have had to adapt from a declining manufacturing industrial base to a service sector led economy. To achieve these changes many cities have undergone urban regeneration policies that have resulted in significant changes to their physical structure and that have in tum affected the social, economic and environmental dynamics of the built environment. One critical dimension of this regeneration of urban areas has been balance between new development and the conservation of historic buildings and townscape. This thesis will therefore consider the application of regeneration policies to historic urban quarters and analyse their effectiveness. The aim of the research is to evaluate the effectiveness of regeneration policies, particularly those applied to urban historic quarters in England since 1997. First of all, this thesis will identify the criteria for positive urban regeneration developed from a thorough literature review of urban regeneration practice. The research will also examine the effectiveness and success of policies and evaluate the influencing factors. Then, these criteria and factors will be examined through two mixed-use regeneration case studies of historic urban quarters in England: the Lace Market in Nottingham and the Jewellery Quarter in Binningham. The thesis will evaluate the regeneration outcomes (physical, economic and social) and the effectiveness of urban policies applied in these two cases will be analysed.